Aggregation-induced photocatalytic activity and efficient photocatalytic hydrogen evolution of amphiphilic rhodamines in water. Issue 43 (13th October 2020) - Shigemitsu, Hajime; Tani, Youhei; Tamemoto, Tomoe; Mori, Tadashi; Li, Xinxi; Osakada, Yasuko; Fujitsuka, Mamoru; Kida, Toshiyuki
Abstract : Simple amphiphilic rhodamines formed supramolecular assemblies and exhibited aggregation-induced photocatalytic activity and hydrogen evolution in water. Abstract : The development of photocatalysts is an essential task for clean energy generation and establishing a sustainable society. This paper describes the aggregation-induced photocatalytic activity (AI-PCA) of amphiphilic rhodamines and photocatalytic functions of the supramolecular assemblies. The supramolecular assemblies consisting of amphiphilic rhodamines with octadecyl alkyl chains exhibited significant photocatalytic activity under visible light irradiation in water, while the corresponding monomeric rhodamines did not exhibit photocatalytic activity. The studies on the photocatalytic mechanism by spectroscopic and microscopic analyses clearly demonstrated the AI-PCA of the rhodamines. Moreover, the supramolecular assemblies of the rhodamines exhibited excellent photocatalytic hydrogen evolution rates (up to 5.9 mmol g −1 h −1 ).